Fertilization success of sterlet Acipenser ruthenus and Siberian sturgeon Acipenser baerii gametes under conditions of heterospecific mating - Havelka, M; Šachlová, H; Shaliutina-Kolešová, A; Rodina, M (Animal reproduction science, 2016)
Species may be prevented from interspecific hybridization by a number of different reproductive barriers that operate precopulatory and postcopulatory. In situation, when natural precopulatory reproductive barriers are affected by anthropogenic factors, postcopulatory reproductive barriers may be important for maintaining gametic isolation and hence preventing interspecific hybridization. This is highly topical in sturgeon (order Acipenseriformes) which exhibits remarkable ease of interspecific hybridization. The objectives of the present study were to evaluate the fertilization success of Acipenser ruthenus and Acipenser baerii spermatozoa under the interspecific competitive conditions and assessed, whether their spermatozoa tend to differentially fertilize eggs of conspecifics. We set up several in vitro fertilization experiments: (i) pooled eggs of both species were fertilized by sperm of each species separately; (ii) eggs of each species were fertilized by pooled sperm; (iii) pooled eggs were fertilized by pooled sperm and (iv) purebred and hybrid control groups. Using parental assignment by molecular markers, we found that when these species competed in pooled sperm, 78.9% of progeny were sired by A. ruthenus and 21.1% by A. baerii, demonstrating higher fertilization success for the former, irrespective of conspecificity of fertilized eggs. When pooled eggs were inseminated by A. ruthenus or A. baerii sperm separately, progeny almost equally comprised hybrid and purebred individuals. Hence, neither A. ruthenus nor A. baerii eggs showed a tendency to biased fertilization by spermatozoa of conspecific males. These findings together show that there may not be postcopulatory mechanisms preventing hybridization between A. ruthenus and A. baerii.
Keywords: hybridizace genetická; Animals; Female; fertilizace in vitro; spermie; ženské pohlaví; interakce spermie a vajíčka; Competitive fertilisation; Spermatozoa; Oocytes; Acipenseriformes; Fishes; oocyty; motilita spermií; ryby; Hybridization, Genetic; Interspecific hybridization; Male; Postcopulatory sexual selection; Sperm Motility; zvířata; mužské pohlaví; Fertilization in Vitro; Sperm-Ovum Interactions